Đáp án:
\(x - 2y - 3 = 0\).
Giải thích các bước giải:
Gọi \(M\left( {x;y} \right) \in d\), gọi \(M'\left( {x';y'} \right) = {T_{\overrightarrow v }}\left( M \right) \Rightarrow \left\{ \begin{array}{l}x' = x + 1\\y' = y - 3\end{array} \right. \Rightarrow \left\{ \begin{array}{l}x = x' - 1\\y = y' + 3\end{array} \right.\).
\( \Rightarrow M\left( {x' - 1;y' + 3} \right)\).
\(M \in d \Rightarrow \left( {x' - 1} \right) - 2\left( {y' + 3} \right) + 4 = 0 \Leftrightarrow x' - 2y' - 3 = 0\).
Gọi \(d' = {T_{\overrightarrow v }}\left( d \right) \Rightarrow M' \in d'\).
Vậy phương trình \(d'\) là \(x - 2y - 3 = 0\).